2-Methylimidazolium pyridine-2, 5-dicarboxylato zinc(II) dihydrate: Synthesis, characterization, DNA interaction, anti-microbial, anti-oxidant and anti-breast cancer studies. Issue 16 (17th December 2021) - Sudha, Dhakshinamoorthy; Vairam, Sundararajan; Sarathbabu, Subbarayan.; Senthil Kumar, Nachimuthu; Sivasamy, Ramasamy; Jone Kirubavathy, Suyambulingam
Abstract: 2-Methylimidazolium pyridine-2, 5-dicarboxylato zinc(II) dihydrate crystal (1 ) is synthesized and characterized by Fourier transform infrared spectroscopy (FTIR), single crystal X-ray diffraction analysis (SCXRD), thermogravimetric-differential thermal analysis (TG-DTA), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), powder X-ray diffraction analysis (PXRD), proton nuclear magnetic resonance ( 1 H NMR) studies, electronic absorption studies (UV-VIS) and DNA interaction studies. 1 was then explored for anti-microbial, anti-oxidant and anti-cancer activity. The SCXRD studies show that the compound crystallizes in the triclinic system and exhibits a distorted octahedral geometry with methyl imidazole ion as the cation. An exothermic decomposition at 400 °C implies high temperature stability in TG-DTA. PXRD confirms the phase purity of the sample. 1 H NMR and UV-VIS results show that the solution structure of 1 is in agreement with SCXRD data. DNA interactions evaluated by agarose gel electrophoresis method substantiate the intercalative mode of binding. Anti-oxidant analysis shows that it exhibits good scavenging ability against DPPH and NO radicals. Anti-microbial activity suggests that 1 has better activity against Escherichia coli than Staphylococcus aureus. Further, the potential anti-cancer activities of complex indicate that the compound has good activity with a half-maximal inhibition concentration (IC50 ) value of 21.3 against MCF-7 human breast cancer cell line, suggesting that it may act as an anti-breast cancer drug. Graphical Abstract: UF0001